1992
DOI: 10.1097/00000658-199212000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Human Growth Hormone in Patients With Severe Sepsis

Abstract: The objective of this study was to evaluate the safety and the effect of recombinant exogenous growth hormone (GH) on nitrogen production in patients with severe sepsis. It was designed as a prospective, randomized, placebo-controlled trial, and performed in the medical intensive care unit of a university hospital. Twenty patients admitted with septic shock and receiving standard parenteral nutrition served as subjects. Treatment consisted of GH 0.1 mg/kg/day or placebo administered as continuous intravenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(40 citation statements)
references
References 35 publications
2
36
0
2
Order By: Relevance
“…Indeed, when critically ill patients were treated with human growth hormone, the mortality rate was increased, suggesting that prevention of muscle breakdown in critical illness may actually be harmful (34). Results in that study, however, are controversial, and in several other reports (21,25,32,38), treatment of critically ill patients with human growth hormone did not result in adverse effects but improved nitrogen balance and wound healing. As suggested by others (30,32) and by Takala et al (34), it is possible that the increased mortality in human growth hormone-treated patients in the study by Takala et al (34) reflected suboptimal control of blood sugar levels rather than prevention of muscle proteolysis.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, when critically ill patients were treated with human growth hormone, the mortality rate was increased, suggesting that prevention of muscle breakdown in critical illness may actually be harmful (34). Results in that study, however, are controversial, and in several other reports (21,25,32,38), treatment of critically ill patients with human growth hormone did not result in adverse effects but improved nitrogen balance and wound healing. As suggested by others (30,32) and by Takala et al (34), it is possible that the increased mortality in human growth hormone-treated patients in the study by Takala et al (34) reflected suboptimal control of blood sugar levels rather than prevention of muscle proteolysis.…”
Section: Discussionmentioning
confidence: 82%
“…However, an early study by Soroff et al [8] in 1967 demonstrated that GH was ineffective during the early ebb phase, but improved nitrogen balance in the anabolic phase of thermal injury. Later, both GH and insulin-like growth factor-1 (IGF-1) have preliminarily been investigated in the severe catabolism seen in septicemia [3,[9][10][11]. The results of these studies indicate that patients who recovered from the initial acute catabolic responses seem to have positive effects of GH.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is also associated with a wide range of hormonal changes that contribute to the catabolic state; among these there is an alteration of the somatotropic axis (47). A decrease in serum concentrations of IGF-I in septic patients and in different inflammatory diseases has also been observed (12,28).…”
mentioning
confidence: 99%